1992
DOI: 10.1111/j.1348-0421.1992.tb02044.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between an 85 kDa Protein and the Protective Effects of Mycoplasma pneumoniae

Abstract: In the immunoblot analysis, sera from patients infected with Mycoplasma pneumoniae reacted with the 168 kDa (P1) and the 85 kDa proteins of virulent strain FH-P24 and P24-S1 mutant strain but not with the 85 kDa protein of P24-S11. Sera of hamsters and BALB/c mice, which had been immunized with live vaccines, were tested. In FH-P24 immunized animals, 100% or 80%, and in P24-S1, 40% of hamsters and 60% of BALB/c mice, developed antibodies against the 85 kDa protein, but antibodies were not detected in sera of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Development of live attenuated vaccines administered intranasally or by aerosol inhalation in animal models showed some protective efficacy against disease upon rechallenge with virulent strains, suggesting that stimulation of local mucosal defense mechanisms is important (123,135,449). Development of a serum antibody response after mucosal immunization may or may not occur, depending on the immunogen (123,135,450). Unfortunately, the live attenuated vaccines never made it to human use due to concern over residual virulence of the vaccine strain of M. pneumoniae.…”
Section: Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of live attenuated vaccines administered intranasally or by aerosol inhalation in animal models showed some protective efficacy against disease upon rechallenge with virulent strains, suggesting that stimulation of local mucosal defense mechanisms is important (123,135,449). Development of a serum antibody response after mucosal immunization may or may not occur, depending on the immunogen (123,135,450). Unfortunately, the live attenuated vaccines never made it to human use due to concern over residual virulence of the vaccine strain of M. pneumoniae.…”
Section: Vaccinesmentioning
confidence: 99%
“…While the importance of the P1 adhesin in mediating M. pneumoniae cytadherence and initiation of disease cannot be denied, animal studies using P1 as a vaccine antigen have not demonstrated protective efficacy (76,(204)(205)(206). Experimental animal studies involving mice (449,450) hamsters (18,(75)(76)(77), guinea pigs (206), and chimpanzees (21,153) have continued through the 1980s and 1990s, but to our knowledge there have been no recent clinical trials in humans with any newer versions of M. pneumoniae vaccines, and there is no indication that any type of vaccine will be approved for use against M. pneumoniae any time soon.…”
Section: Vaccinesmentioning
confidence: 99%
“…We have considerable evidence that the two proteins B and C are identical with the cleavage fragments of the open reading frame 6 (ORF6) gene product (40-and 90-kDa proteins) of the P1 operon, which consists of three ORFs in the order ORF4, ORF5 (P1), ORF6 (11,17,19,21,22,26,27,35,43). Biochemical and immunological studies revealed the location of the ORF6 gene product at the tip-like organelle of M. pneumoniae in close proximity to the P1 protein (11,26,27).…”
mentioning
confidence: 99%
“…Characterization of spontaneously cytadherence-negative mutants (9,21,22) or comparable mutants obtained after nitrosoguanidine treatment (12,13,43) resulted in the identification of proteins which are necessary for effective adherence to host cells. In addition to the adhesin P1 (170 kDa) and the adhesin-related 30-kDa protein (3,4,7,10,15,16,18,40), which are not sufficient for M. pneumoniae cytadherence, three membrane proteins of 85, 72, and 37 kDa (designated B, A, and C, respectively, by Hansen et al [12]) and five proteinaceous components (HMW1 to -5) of the cytoskeleton-like triton shell are involved in the attachment process (17,24,30,(35)(36)(37)(38)43). These proteins are generally designated accessory proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation